(untitled) (European Journal of Marketing and Economics, 2021)
Each banking institution has a customer-oriented strategic plan, although the sudden emergence of competition does not allow them to relax. The explosion of new technologies and the rise in consumer demand have been putting pressure on banks since the 2008 recession. Retail banking customers are constantly expecting new, improved, affordable, convenient continuous service from the bank. In an environment of increasingly competitive, innovative financial services, banks need to be able to maintain not only customers but also brand awareness. The emergence of non-traditional financial service providers in the market such as FinTech, NEO Banks, Challenger Banks, BigTech, which reduces the relationship between banks and their customers, completely changes the banking industry. Today we face a new open ecosystem of consumers, traditional banks, FinTech and BigTech companies, regulators, developers, non-banking firms and other players, with customers at the center. Banks will have to significantly change their commercial and operating models to retain customers and remain active players in the market. The presented paper examines the development trends of new players in the financial industry - non-traditional financial service providers and the readiness of the banking industry to respond to these trends. The paper is a study of the impact of digitalization of financial services on the banking sector based on the study and analysis of reports of the various international organizations, local policy documents, reports and regulations of the National Bank, the papers of various researchers and their secondary data. Based on the research, suggestions have been made on how Georgian banks should strategically approach non-traditional providers of financial services to avoid losses, withstand competition and remain active market players.